A Photoswitchable Trivalent Cluster Mannoside to Probe the Effects of Ligand Orientation in Bacterial Adhesion - Despras, Guillaume; Möckl, Leonhard; Heitmann, Anne; Stamer, Insa; Bräuchle, Christoph; Lindhorst, Thisbe K. (ChemBioChem, 2019)
We have recently demonstrated, by employing azobenzene glycosides, that bacterial adhesion to surfaces can be switched through reversible reorientation of the carbohydrate ligands. To investigate this phenomenon further, we have turned here to more complex—that is, multivalent—azobenzene glycoclusters. We report on the synthesis of a photosensitive trivalent cluster mannoside conjugated to an azobenzene hinge at the focal point. Molecular dynamics studies suggested that this cluster mannoside, despite the conformational flexibility of the azobenzene-glycocluster linkage, offers the potential for reversibly changing the glycocluster's orientation on a surface. Next, the photoswitchable glycocluster was attached to human cells, and adhesion assays with type 1 fimbriated Escherichia coli bacteria were performed. They showed marked differences in bacterial adhesion, dependent on the light-induced reorientation of the glycocluster moiety. These results further underline the importance of orientational effects in carbohydrate recognition and likewise the value of photoswitchable glycoconjugates for their study.
CRIS-Team Scopus Importer:2024-09-09
Keywords: cell adhesion; control of carbohydrate recognition; metabolic oligosaccharide engineering; multivalency; photochemistry